Music Teacher Training during the process of European Convergence in Higher Education in Poland, Hungary and the Czech Republic - Vicente, Alejandro; Subirats, Maria dels Ángels; Ibarra, Julia (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article tries to reflect about the status of teacher training in music education in three Eastern European countries with a long musical tradition, and how these countries are morphing to the current requirements of the Bologna Process in European Higher Education. Although the final outcome of the new programmes in these three countries is still uncertain, it is possible to foresee that music education will continue to be extensively taken into account as much as it has been in the past, giving the utmost importance to train music teachers